Inhabituel. - Agnello, Chiara; Parisi, Chiara; Pinto, Roberto; Obrist, Hans Ulrich; Maffesoli, Michel; Setari, Nicola; Debray, Régis; Fabbrica del Vapore, Milan; Le Centre culturel français de Milan, Milan (Paris : Dena Foundation for Contemporary Art, 2005)
Agnes, Rebecca ; Agostini, Nicoletta ; Balula, David ; Gréaud, Loris ; Benassi, Elisabetta ; Bertocchi, Davide ; Boggeri, Dafne ; Chang, Hsia-Fei ; Dafni & Papadatos ; Ghazel ; Hosking, Mark ; et al.
Fabbrica del Vapore, Milan, February 18th - March 6th 2005 / Le Centre culturel français de Milan, Milan, March 2nd - 6th 2005
kunstcatalogus